Etiquette of speech in works of Eastern scholars Beruni, Ibn Sina, Al Khorazmi, Alisher Navoi and its importance in human education (Genius Repository, 2023)
Language is the spiritual wealth of the nation. Language is not only a tool for problems, but also a people's culture, traditions, lifestyle, and history. Eastern thinkers recommend to the orator to study the language in depth, to master its vocabulary and grammar, to learn to speak logically, to pay equal attention to the internal and external appearance (form and content) of the speech, to be fluent and expressive. they set the tasks of being able to make a secret speech, using language resources appropriately and purposefully. Eastern thinkers, first of all, as civilized people, studied the science of oratory, expressed instructive thoughts about the power of words, and followed the rules of this oratory. In order to develop our speech culture, it is necessary to study the views of Eastern thinkers on speech etiquette.